The construction of early career teachers’ identities: coping or managing? - Hong, Ji; Day, Christopher; Greene, Barbara (Taylor & Francis, 2017)
This paper examines how early career teachers cope with or manage the challenges that they experience during the transition from pre-service to the first and then the second year of teaching as they seek to establish stable, positive, professional identities and teach effectively in various school and policy contexts. Findings from three waves of interviews conducted with six elementary and secondary school teachers showed that, for these teachers in the early years of teaching, the construction of positive or negative, stable or unstable professional identities was closely related to whether they coped with or managed various tensions and to their perceived effectiveness. The findings also revealed that their ability to cope or manage was not only influenced by the relative strength of commitment with which they entered teaching, but also by the kinds of school-level support which they experienced.